2011
DOI: 10.1016/j.ejor.2011.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Group and individual heterogeneity in a stochastic frontier model: Container terminal operators

Abstract: Container ports are a major component of international trade and the global supply chain. Hence, the improvement of port efficiency can have a significant impact on the wider maritime economy. This paper deconstructs a representation in the existing literature that neglects the heterogeneity of individual and group-specific terminal operators. In its place, we present a hierarchical model to make a connection between efficiency and terminal operator group characteristics. The paper develops a stochastic fronti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This association can occur due to the high overall workload to which dock workers are exposed. Study of different categories (health workers) showed that one of the ways of reducing the use of drugs such as tobacco and psychoactive substances, could be to reduce the workload, demonstrating that the drug issue should be addressed in the workplace 27 . The results of this research instigates further study the specificity the relation between lifestyle, wellness in / work and productivity.…”
Section: Discussionmentioning
confidence: 70%
“…This association can occur due to the high overall workload to which dock workers are exposed. Study of different categories (health workers) showed that one of the ways of reducing the use of drugs such as tobacco and psychoactive substances, could be to reduce the workload, demonstrating that the drug issue should be addressed in the workplace 27 . The results of this research instigates further study the specificity the relation between lifestyle, wellness in / work and productivity.…”
Section: Discussionmentioning
confidence: 70%
“…Stochastic frontier analysis (SFA) is a parametric and stochastic approach to estimate productive efficiency. The major breakthrough of SFA compared to regression methods is that SFA calculates the inefficiency of DMUs based on distribution assumptions, so different entities can have different inefficiencies (Yip et al, 2011;Merkel, 2018). In common with the COLS approach, SFA relaxes the assumption that the behavior of DMUs is optimized.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has not sufficiently addressed efficiency changes in large Asian container ports compared with those in developed regions. Few studies have tried to analyze the sources to which efficiency gains and losses can be attributed (Cullinane et al, 2002;Yip et al, 2011). In this study, we aim to fill these gaps by estimating the efficiency changes of major Asian container ports, many of which are along the Silk Road Economic Belt, for the period from 2000 to 2007.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical parametric method, the SFA considers the errors caused by statistics and observations. However, the presumed frontier function has certain subjectivity [26]. The evaluation indicators are uncertain in either the parametric or the nonparametric method for port performance evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%